PPy thin layer coated sulfur vacancy-containing Mn0. 2Cd0. 8S nanoparticle composite material as well as preparation method and application thereof

By wrapping the PPy thin layer on the surface of Mn0.2Cd0.8S nanoparticles containing sulfur-containing vacancy, forming a composite material, solving the problems of agglomeration, insufficient active sites and low carrier efficiency of Mn0.2Cd0.8S photocatalytic materials, and achieving a significant improvement in photocatalytic activity.

CN120132915APending Publication Date: 2025-06-13HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510299898.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

The existing Mn0.2Cd0.8S photocatalytic materials have problems such as easy agglomeration, fewer surfactant sites and poor carrier separation and transfer efficiency, which affect their photocatalytic activity.

Method used

The sulfur-containing vacancy Mn0.2Cd0.8S nanoparticles were generated by in-situ hydrothermal method, and a PPy thin layer was wrapped on the surface to form a sulfur-containing vacancy Mn0.2Cd0.8S nanoparticle composite material wrapped in the PPy thin layer.

Benefits of technology

The photogenerated electron-hole separation efficiency is improved, the visible light absorption range is expanded, the mass transfer speed is improved, the photocatalytic activity is significantly improved, and the ciprofloxacin in water can be efficiently removed and highly active H2O2 can be produced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120132915A_ABST
    Figure CN120132915A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of inorganic nano composite materials, and discloses a PPy thin layer wrapped sulfur vacancy-containing Mn0. 2Cd0. 8S nano particle composite material, a preparation method and application, firstly, Mn0. 2Cd0. 8S nano particles are prepared through a solvothermal method, hydrazine monohydrate is added as a reducing agent to introduce sulfur vacancy, then the sulfur vacancy-containing Mn0. 2Cd0. 8S nano particles are put into water to be subjected to ultrasonic dispersion, and the PPy thin layer wrapped sulfur vacancy-containing Mn0. 2Cd0. 8S nano particle composite material is obtained. And sequentially adding CTAB (Cetyltrimethyl Ammonium Bromide), pyrrole and an ammonium persulfate solution into the dispersion liquid to obtain the Mn0. 2Cd0. 8S nano-particle composite material coated with a PPy thin layer and containing sulfur vacancies, and applying the Mn0. 2Cd0. 8S nano-particle composite material to photocatalytic degradation of ciprofloxacin and production of H2O2. Sulfur vacancies are introduced into Mn0. 2Cd0. 8S, the surface of Mn0. 2Cd0. 8S is wrapped with PPy, a tight contact interface is formed, the light absorption performance is improved through the synergistic effect between Mn0. 2Cd0. 8S and PPy, and therefore the photocatalytic activity of the composite structure is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inorganic nanocomposite materials, and in particular to a PPy thin layer-wrapped sulfur-containing vacancy Mn 0.2 Cd 0.8 S nanoparticle composite materials, preparation methods and applications. Background Art

[0002] With the rapid development of industrial level, the amount of pollutants generated by various industries around the world has increased dramatically. Pollutant emissions have become one of the main sources of environmental pollution, and the problem of water pollution needs to be solved urgently. Photocatalytic technology has the characteristics of low cost, high efficiency, recyclability, and environmental protection. It is one of the best methods for pollutant treatment and has received widespread attention. Under the action of solar energy, full-spectrum driven photocatalytic technology provides a sophisticated solution to solve environmental pollution and convert it into alternative energy forms. Therefore, the design and application of efficient catalytic materials are key factors in promoting the industrialization of photocatalytic technology.

[0003] Mn 0.2 Cd 0.8 S, a ternary sulfide solid solution that combines the advantages of narrow bandgap cadmium sulfide (2.4 eV) and wide bandgap manganese sulfide (3.7 eV), has good chemical stability and environmentally friendly properties, easy to control morphology, large specific surface area, and stronger stability. It is an ideal visible light-driven photocatalytic material. The formation of metal sulfide solid solution is an effective way to remove antibiotics from water and can effectively reduce the content of quinolone pollutants in water. However, single Mn 0.2 Cd 0.8 In the catalytic materials of S, the problems of easy agglomeration, few surface active sites and poor carrier separation and transfer efficiency seriously affect its photocatalytic activity. The study found that the use of precious metal surface deposition, ion doping and composite structure with other semiconductor materials to build a composite structure can effectively improve the photocatalytic activity of Mn 0.2 Cd 0.8 S modification can effectively improve its photocatalytic activity. Among them, the composite structure constructed with other semiconductor materials can not only broaden the light response range of photocatalytic materials and improve the utilization rate of solar energy, but also the effective interface bonding formed by the composite structure can effectively realize the separation of photogenerated electron pairs, greatly improving the photocatalytic activity. Therefore, compared with other modification methods, constructing composite structure materials is a more effective and economical method. However, the selection of semiconductors with suitable band gap positions and Mn 0.2 Cd 0.8 S complex and constructing a close contact interface are the key to obtaining an efficient photocatalytic active system.

[0004] Polypyrrole (PPy) is one of the most common conductive polymers, with advantages such as a moderate bandgap (2.45 eV), high conductivity, good environmental stability, non-toxicity, low cost, and easy preparation. Researchers have found that due to the presence of nitrogen atoms and the high surface energy of polypyrrole, there are positive charges in polypyrrole, making it an ideal adsorption material for ion exchange with anions in aqueous solutions. Based on these properties, researchers have begun to study the application of polypyrrole polymers in water pollutant treatment. However, in single PPy catalytic materials, problems such as low photonic yield and high recombination rate of photogenerated carriers seriously affect their photocatalytic activity. Summary of the Invention

[0005] Object of the Invention: Aiming at the problems existing in the prior art, the present invention provides a sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles composite material wrapped with a PPy thin layer, a preparation method and an application thereof. First, sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles are generated by an in-situ hydrothermal method, and then surfactant CTAB, pyrrole, and ammonium persulfate (APS) solution are sequentially and slowly added to the sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticle dispersion under stirring conditions, and a sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticle composite material wrapped with a PPy thin layer is obtained by stirring and regulating experimental conditions, and it is used as a photocatalyst for removing harmful antibiotic ciprofloxacin in water under visible light and producing highly active H 2 O 2 . The material prepared by the present invention has good light absorption performance and photocatalytic activity.

[0006] Technical Solution: In the first aspect, the present invention provides a preparation method of a sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticle composite material wrapped with a PPy thin layer, comprising the following steps: S1. Take Cd(NO 3 ) 2 ·4H 2 O, Mn(NO 3 ) 2 ·4H 2 O and thiourea, add them to a mixed solution of deionized water and ethylenediamine, and stir evenly; then add hydrazine monohydrate and stir evenly to obtain a mixed solution; after hydrothermal reaction of the mixed solution, cool, wash, and dry to obtain sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles; S2. The sulfur-vacancy-containing Mn 0.2 Cd 0.8After mixing S nanoparticles with deionized water, add surfactant CTAB and sonicate; then add pyrrole and continue stirring until completely dissolved; next, slowly add ammonium persulfate solution to the above solution under an ice-water bath, stir, and carry out a polymerization reaction; centrifuge, wash, and dry to obtain a sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticle composite material.

[0007] Further, in S1, the dosage ratio of Cd(CH 3 COO) 2 ·2H 2 O, Mn(CH 3 COO) 2 ·4H 2 O, thiourea, deionized water, ethylenediamine, and hydrazine monohydrate is 0.0757 - 47.2801 g∶0.0201 - 12.5512 g∶0.0913 - 57.0923 g∶10 - 1000 mL∶10 - 1000 mL∶0.2 - 100 mL.

[0008] Further, in S1, the volume ratio of the deionized water to ethylenediamine is 1∶1.

[0009] Further, in S1, the specific conditions of the hydrothermal reaction are: the reaction temperature is 160 - 220 °C, and the reaction time is 16 - 32 h.

[0010] Further, in S2, the dosage ratio of the sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles, deionized water, CTAB, pyrrole, and ammonium persulfate is 0.0531 g - 33.1500 g∶20 - 2000 mL∶0.0085 g - 5.3125 g∶1 - 200 μL∶5 - 2800 mL.

[0011] Further, in S2, the concentration of the ammonium persulfate solution is 0.1 mol·L -1 .

[0012] Preferably, in S2, the specific conditions of the polymerization reaction are: reacting at room temperature for 8 - 16 h.

[0013] In a second aspect, the present invention provides a PPy thin-layer-coated sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticle composite material, the composite material is prepared by the method described in any one of the above, and the microscopic morphology of the composite material is sulfur-vacancy-containing Mn 0.2 Cd 0.8The S nanoparticles are wrapped with a layer of PPy nanofilm; wherein, the mass ratio of PPy in the composite material is 3‰ - 18‰.

[0014] Thirdly, the present invention provides a sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticle composite material prepared by the method as described in any one of the above for degrading ciprofloxacin in a solution under visible light and producing H 2 O 2 in pure water.

[0015] Theoretical explanation: The present invention first prepares sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles by a solvothermal method, introduces sulfur vacancies by adding hydrazine hydrate as a reducing agent, and then disperses the sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles in water by ultrasonic dispersion. Subsequently, surfactants CTAB, pyrrole, and ammonium persulfate (APS) solution are sequentially and slowly added to the dispersion of sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles under stirring conditions, and a composite material of sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles wrapped with a PPy thin layer is obtained by stirring at room temperature, and it is used to remove harmful antibiotic ciprofloxacin in water body and produce highly active H 2 O 2 .

[0016] In the composite material prepared by the present invention, PPy and sulfur-vacancy-containing Mn 0.2 Cd 0.8 S have good band gap matching, thereby constructing a Z-scheme heterojunction, significantly improving the separation efficiency of photo-generated electrons and holes, expanding the visible light absorption range, improving the mass transfer rate, and enhancing the photocatalytic activity. By in-situ hydrothermal wrapping of PPy on the surface of Mn 0.2 Cd 0.8 S nanoparticles, uniform loading of PPy on the surface of Mn 0.2 Cd 0.8 S nanoparticles can be realized, forming a tight contact interface to enhance the separation of photo-generated charges, increasing the specific surface area and active sites of the composite structure. At the same time, the synergistic effect between the two can be utilized to improve the light absorption performance, thus greatly enhancing the photocatalytic activity of the composite structure.

[0017] Beneficial effects: Compared with the prior art, the specific beneficial effects of the present invention are as follows: (1) The present invention first proposes a composite material of sulfur-vacancy-containing Mn 0.2 Cd 0.8S nanoparticle composite materials, and a preparation method of the novel composite structural material is also provided.

[0018] (2) For the first time, the present invention composes Mn 0.2 Cd 0.8 S nanoparticles with PPy polymer materials, effectively broadening the light response range of the composite structural material. The prepared Mn 0.2 Cd 0.8 S nanoparticles composite material wrapped with a PPy thin layer has high visible light absorption performance, improving the utilization efficiency of sunlight.

[0019] (3) For the first time, the present invention uses an in-situ hydrothermal method to coat a PPy nano-layer on the surface of Mn 0.2 Cd 0.8 S nanoparticles, which can expand the specific surface area of Mn 0.2 Cd 0.8 S nanoparticles, increase the surface active reaction sites, inhibit the recombination of electron-hole pairs, are beneficial to the adsorption of ciprofloxacin molecules on the surface of the composite structural material, and improve the reaction rate of the redox reaction to achieve a more excellent photocatalytic effect.

[0020] (4) The prepared Mn 0.2 Cd 0.8 S nanoparticles composite material wrapped with a PPy thin layer can be used as a catalyst for the degradation of ciprofloxacin and the production of hydrogen peroxide under visible light. Among them, when the mass ratio of PPy is 9‰, under visible light irradiation for 1 h, the removal efficiency of ciprofloxacin is 97.1%; for the production of hydrogen peroxide, when irradiated with visible light in pure water for 2 h, the H 2 O 2 production is 1717.7 μM, and its catalytic activity is far superior to that of the two monomers.

[0021] (5) The preparation process of the present invention is green and simple, the raw materials and the final products are all non-toxic and harmless, there is no secondary pollution, the reaction conditions are mild and easy to control, and the stability is good. It has broad application prospects in solving water pollution. Description of the Drawings Figure 1 is the XRD pattern of Mn 0.2 Cd 0.8 S nanoparticles with sulfur vacancies and the Mn 0.2 Cd 0.8 S nanoparticles composite material wrapped with a PPy thin layer prepared in Examples 1, 3 and 5; Figure 2 is the Mn 0.2 Cd 0.8 S nanoparticles with sulfur vacancies and the Mn 0.2 Cd0.8 EPR diagram of S nanoparticle composite Figure 3 For Mn with sulfur vacancies 0.2 Cd 0.8 S nanoparticles, PPy nanoparticles and Mn with sulfur vacancies wrapped by PPy thin layer prepared in Example 3 0.2 Cd 0.8 UV-VIS diagram of Mn with sulfur vacancies wrapped by PPy thin layer prepared in Example 3 Figure 4 For Mn with sulfur vacancies wrapped by PPy thin layer prepared in Example 3 0.2 Cd 0.8 Effect diagram of ciprofloxacin degradation (left) and hydrogen peroxide production (right) of Mn with sulfur vacancies wrapped by PPy thin layer prepared in Example 3 through four-cycle experiments under visible light Figure 5 For Mn with sulfur vacancies 0.2 Cd 0.8 S nanoparticles, PPy nanoparticles and Mn with sulfur vacancies wrapped by PPy thin layer prepared in Example 4 0.2 Cd 0.8 Transient photocurrent diagram of Mn with sulfur vacancies wrapped by PPy thin layer prepared in Example 4 Figure 6 For Mn with sulfur vacancies 0.2 Cd 0.8 S nanoparticles (a) and SEM diagram of Mn with sulfur vacancies wrapped by PPy thin layer prepared in Example 5 0.2 Cd 0.8 S nanoparticle composite (b) Detailed implementation mode

[0023] The present invention will be introduced in detail below in combination with the implementation mode

[0024] In the present invention, the experiments of ciprofloxacin degradation and hydrogen peroxide production under visible light are carried out in a GHX-3 type photoreactor, using a 300 W xenon lamp to simulate the solar light source, and filtering out ultraviolet light with a filter with λ>420 nm to evaluate the removal efficiency of ciprofloxacin molecules in the solution and the hydrogen peroxide production rate of the Mn with sulfur vacancies wrapped by PPy thin layer prepared in the present invention 0.2 Cd 0.8 S nanoparticle composite

[0025] The specific steps of the ciprofloxacin molecule removal experiment in the solution are as follows: Take 70 mL of 10 mg / L ciprofloxacin solution, measure its initial value, and then add 20 mg of Mn with sulfur vacancies 0.2 Cd 0.8For the S nanoparticle / PPy nanocomposite material, after a period of dark reaction to reach the adsorption-desorption equilibrium, turn on the light and take samples at regular intervals. After centrifugal separation, take the supernatant. Measure the absorbance at the maximum absorption wavelength (λ Cr = 271 nm) in a UV-visible spectrophotometer, and then calculate the removal efficiency of ciprofloxacin molecules based on the change in absorbance before and after illumination.

[0026] The specific steps for the experiment of producing hydrogen peroxide from pure water are as follows: Add 50 mL of water to the reactor, and then add 20 mg of Mn with sulfur vacancies 0.2 Cd 0.8 S nanoparticle / PPy nanocomposite material (the added amount), turn on the light and take samples at regular intervals. After centrifugal separation, take the supernatant. Measure the absorbance at the maximum absorption wavelength (λ MO = 352 nm) in a UV-visible spectrophotometer, and then calculate the yield of hydrogen peroxide based on the change in absorbance before and after illumination.

[0027] Example 1: This example provides a preparation method for a composite material of Mn with sulfur vacancies 0.2 Cd 0.8 S nanoparticles wrapped with a PPy thin layer, which is as follows: (1) Weigh 0.0757 g of Cd(CH 3 COO) 2 ·2H 2 O, 0.0201 g of Mn(CH 3 COO) 2 •2H 2 O and 0.0913 g of thiourea and add them to a mixed solution of deionized water and ethylenediamine (10 mL each of water and ethylenediamine), and ultrasonically stir for 0.5 h each. Subsequently, add 0.2 mL of hydrazine monohydrate (N 2 H 4 ·H 2 O) to the mixture, continue to stir for 0.5 h, and then transfer the mixed solution to a polytetrafluoroethylene-lined autoclave and react at 160 °C for 32 h. After the reaction is completed, naturally cool to room temperature. Filter the sample, wash it several times with deionized water and absolute ethanol, and then transfer it to an oven for vacuum drying for a period of time to obtain Mn with sulfur vacancies 0.2 Cd 0.8 S nanoparticles.

[0028] (2) The Mn with sulfur vacancies obtained in step (1) 0.2 Cd 0.8S nanoparticles were added to 20 mL of deionized water, ultrasonicated and stirred for 20 min, then 0.0085 g of surfactant CTAB was added and ultrasonicated for 20 min, and then 1 μL of pyrrole was added and stirred for another 20 min until completely dissolved. Then, 5 mL of 0.1 mol·L -1 ammonium persulfate (APS) solution was slowly added dropwise to the above solution under an ice-water bath, and the stirring polymerization reaction was carried out for 8 h. After the reaction, centrifugation was performed, and the obtained product was washed several times alternately with deionized water and absolute ethanol by centrifugation, and then dried in an oven at 60 °C for 12 h. The dark green powder obtained after sufficient grinding was a composite material of Mn 0.2 Cd 0.8 S nanoparticles wrapped with a PPy thin layer, where the mass ratio of PPy in the composite catalyst was 3‰.

[0029] Figure 1 For the XRD pattern of the Mn 0.2 Cd 0.8 S nanoparticles composite material wrapped with a PPy thin layer prepared in Example 1, it can be seen that the XRD pattern of the sample in Example 1 was basically consistent with that of Mn 0.2 Cd 0.8 S with sulfur vacancies, having matching characteristic peaks, while the peaks of PPy were basically absent, which was due to the low content of pyrrole. This indicated that the successful synthesis of the Mn 0.2 Cd 0.8 S nanoparticles composite material wrapped with a PPy thin layer did not change the crystal structure of the Mn 0.2 Cd 0.8 S monomer with sulfur vacancies.

[0030] The Mn 0.2 Cd 0.8 S nanoparticles with sulfur vacancies (Vs-Mn 0.2 Cd 0.8 S), PPy, and the Mn 0.2 Cd 0.8 S nanoparticles composite material wrapped with a PPy thin layer prepared according to Example 1 had photocatalytic degradation efficiencies of 46.8%, 2.0%, and 93.8% for ciprofloxacin after 1 h of visible light irradiation, respectively.

[0031] For hydrogen peroxide production, the Mn 0.2 Cd 0.8 S nanoparticles with sulfur vacancies, PPy, and the Mn 0.2 Cd 0.8 S nanoparticles composite material wrapped with a PPy thin layer prepared according to Example 1 had hydrogen peroxide yields of 181.2 μM, 18.9 μM, and 928.8 μM, respectively, after 2 h of visible light irradiation.

[0032] From the above catalytic experiment results, it can be seen that the visible light catalytic activity of the prepared composite material of sulfur vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles wrapped with PPy thin layer is significantly improved compared with that of sulfur vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles and PPy monomers.

[0033] Example 2: This example provides a preparation method for a composite material of sulfur vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles wrapped with PPy thin layer, which is as follows: (1) Weigh 0.3783 g of Cd(CH 3 COO) 2 ·2H 2 O, 0.1004 g of Mn(CH 3 COO) 2 •2H 2 O and 0.4567 g of thiourea, and add them to a mixed solution of deionized water and ethylenediamine (15 mL each of water and ethylenediamine), and ultrasonically stir for 0.5 h each. Subsequently, add 1 mL of hydrazine monohydrate (N 2 H 4 ·H 2 O) to the mixture, continue stirring for 0.5 h, then transfer the mixed solution to a polytetrafluoroethylene-lined autoclave, react at 180 °C for 28 h, naturally cool to room temperature after the reaction ends, filter the sample, wash it several times with deionized water and absolute ethanol, and then transfer it to an oven for vacuum drying for a period of time to obtain sulfur vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles.

[0034] (2) Add the sulfur vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles obtained in step (1) to 50 mL of deionized water, ultrasonically stir and stir for 20 min, then add 0.0425 g of surfactant CTAB and ultrasonically stir for 20 min, and then add 2 μL of pyrrole and continue stirring for 20 min until completely dissolved. Then, slowly drop 25 mL of 0.1 mol·L -1 ammonium persulfate (APS) solution into the above solution under an ice-water bath, carry out a stirring polymerization reaction for 12 h, centrifuge after the reaction ends, wash the obtained product alternately several times with deionized water and absolute ethanol by centrifugation, and then dry it in an oven at 60 °C for 12 hours. The dark green powder obtained after sufficient grinding is the composite material of sulfur vacancy-containing Mn 0.2 Cd0.8 S nanoparticle composite, where the mass ratio of PPy in the composite catalyst is 6‰.

[0035] The sulfur vacancy-containing Mn prepared with a PPy thin layer coating according to Example 2 0.2 Cd 0.8 After 1 h of visible light irradiation, the photocatalytic degradation efficiency of the S nanoparticle composite against ciprofloxacin is 92.1%. After 2 h of visible light irradiation, the yield of hydrogen peroxide is 1017.1 μM.

[0036] Example 3: This example provides a preparation method for a sulfur vacancy-containing Mn 0.2 Cd 0.8 S nanoparticle composite, which is as follows: (1) Weigh 1.8912 g of Cd(CH 3 COO) 2 ·2H 2 O and 0.502 g of Mn(CH 3 COO) 2 •2H 2 O and 2.2836 g of thiourea and add them to a mixed solution of deionized water and ethylenediamine (30 mL each of water and ethylenediamine), and ultrasonically stir for 0.5 h each. Subsequently, add 5 mL of hydrazine monohydrate (N 2 H 4 ·H 2 O) to the mixture, continue stirring for 0.5 h, then transfer the mixed solution to a polytetrafluoroethylene-lined autoclave, react at 200 °C for 24 h, and after the reaction is completed, naturally cool to room temperature. Filter the sample, wash it several times with deionized water and absolute ethanol, and then transfer it to an oven for vacuum drying for a period of time to obtain sulfur vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles.

[0037] (2) Add the sulfur vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles obtained in step (1) to 380 mL of deionized water, ultrasonically stir and stir for 20 min, then add 0.2125 g of surfactant CTAB and ultrasonically stir for 20 min, and then add 7 μL of pyrrole and continue stirring for 20 min until completely dissolved. Then, slowly add 112 mL of 0.1 mol·L -1Ammonium persulfate (APS) solution was used for stirring polymerization reaction for 14 h. After the reaction, centrifugation was carried out. The obtained product was washed alternately with deionized water and absolute ethanol by centrifugation for several times, and then dried in an oven at 60 °C for 12 hours. The dark green powder obtained after sufficient grinding was Mn with sulfur vacancies wrapped by PPy thin layer 0.2 Cd 0.8 S nanoparticle composite material, where the mass ratio of PPy in the composite catalyst is 9‰.

[0038] The Mn with sulfur vacancies wrapped by PPy thin layer was prepared according to Example 3 0.2 Cd 0.8 For the S nanoparticle composite material, after visible light irradiation for 1 h, the photocatalytic degradation efficiency of ciprofloxacin was 97.1%. After visible light irradiation for 2 h, the yield of hydrogen peroxide was 1717.7 μM.

[0039] Figure 1 , the Mn with sulfur vacancies wrapped by PPy thin layer was prepared according to Example 3 0.2 Cd 0.8 In the XRD pattern of the S nanoparticle composite material, it can be seen that the XRD pattern of the sample in Example 3 is basically the same as that of Mn with sulfur vacancies 0.2 Cd 0.8 S pattern, with matching characteristic peaks, while the peak of PPy is basically absent, which is due to the small content of pyrrole. This indicates that the successful synthesis of the Mn with sulfur vacancies wrapped by PPy thin layer 0.2 Cd 0.8 S nanoparticle composite material did not change the crystal structure of the Mn with sulfur vacancies 0.2 Cd 0.8 S monomer.

[0040] Figure 2 For the Mn with sulfur vacancies wrapped by PPy thin layer prepared according to Example 3 0.2 Cd 0.8 S nanoparticle composite material's EPR diagram. It can be seen from the diagram that by wrapping PPy on the surface of the Mn with sulfur vacancies 0.2 Cd 0.8 S nanoparticles, the composite structure successfully introduced defects, increased the surface active sites of the catalyst, and improved the reaction efficiency.

[0041] Figure 3 For the Mn with sulfur vacancies wrapped by PPy thin layer prepared according to Example 3 0.2 Cd 0.8 S nanoparticle composite material's UV-VIS diagram. It can be seen from the diagram that by wrapping PPy on the surface of the Mn with sulfur vacancies 0.2 Cd 0.8On the surface of S nanoparticles, the synthesis of the composite structure expands the visible light absorption range of the material and has better visible light response.

[0042] Figure 4 Sulfur vacancy-containing Mn wrapped with PPy thin layer prepared according to Example 3 0.2 Cd 0.8 Efficiency diagrams of the CdS nanoparticle composite wrapped with PPy thin layer obtained in Example 3 for removing ciprofloxacin (left) and producing hydrogen peroxide (right) under visible light after four cycles. It can be seen from the figure that the CdS nanoparticle composite wrapped with PPy thin layer obtained in Example 3 0.2 Cd 0.8 still maintains high activity for ciprofloxacin and hydrogen peroxide production after four cycles, indicating its high stability and recyclability.

[0043] Example 4: This example provides a preparation method for a sulfur vacancy-containing Mn 0.2 Cd 0.8 S nanoparticle composite wrapped with a PPy thin layer, which is as follows: (1) Weigh 9.4560 g of Cd(CH 3 COO) 2 ·2H 2 O, 2.5100 g of Mn(CH 3 COO) 2 •2H 2 O and 11.4180 g of thiourea and add them to a mixed solution of deionized water and ethylenediamine (160 mL each of water and ethylenediamine), and ultrasonically stir for 0.5 h each. Subsequently, add 20 mL of hydrazine monohydrate (N 2 H 4 ·H 2 O) to the mixture, continue stirring for 0.5 h, then transfer the mixed solution to a polytetrafluoroethylene-lined autoclave, react at 200 °C for 24 h, naturally cool to room temperature after the reaction ends, filter the sample, wash it several times with deionized water and absolute ethanol, and then transfer it to an oven for vacuum drying for a period of time to obtain sulfur vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles.

[0044] (2) Add the sulfur vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles obtained in step (1) to 780 mL of deionized water, ultrasonically stir for 20 min, then add 1.0625 g of surfactant CTAB and ultrasonically stir for 20 min, then add 200 μL of pyrrole and continue stirring for 20 min until completely dissolved. Then, slowly add 560 mL of 0.1 mol·L-1 An ammonium persulfate (APS) solution was used for a stirring polymerization reaction for 10 h. After the reaction ended, centrifugation was carried out. The obtained product was alternately washed several times with deionized water and absolute ethanol by centrifugation, and then dried in an oven at 60 °C for 12 hours. After sufficient grinding, the dark green powder obtained was Mn with sulfur vacancies wrapped by a PPy thin layer 0.2 Cd 0.8 CdS nanoparticle composite material, where the mass ratio of PPy in the composite catalyst is 15 ‰.

[0045] Figure 5 It is the Mn with sulfur vacancies wrapped by a PPy thin layer prepared according to Example 4 0.2 Cd 0.8 CdS nanoparticle composite material and the transient photocurrent diagrams of two monomers. It can be seen from the figure that when PPy is wrapped on the surface of Vs-Mn 0.2 Cd 0.8 CdS nanoparticles, the photocurrent generated by the composite structure sample under illumination conditions is significantly enhanced compared with the two monomers, indicating that the composite is beneficial to improving the separation of its photogenerated charges and enhancing the photocatalytic activity.

[0046] The prepared Mn with sulfur vacancies obtained according to Example 4 0.2 Cd 0.8 The photocatalytic degradation efficiency of the CdS nanoparticles / PPy nanocomposite material for ciprofloxacin is 95.7% after 1 h of visible light irradiation. After 2 h of visible light irradiation, the yield of hydrogen peroxide is 1517.1 μM.

[0047] Example 5: This example provides a preparation method of a Mn with sulfur vacancies wrapped by a PPy thin layer 0.2 Cd 0.8 CdS nanoparticle composite material, which is specifically as follows: (1) Weigh 47.2801 g of Cd(CH 3 COO) 2 ·2H 2 O and 12.5512 g of Mn(CH 3 COO) 2 •2H 2 O and 57.0923 g of thiourea were added to a mixed solution of deionized water and ethylenediamine (1000 mL each of water and ethylenediamine), and ultrasonic stirring was carried out for 0.5 h each. Subsequently, 100 mL of hydrazine monohydrate (N 2 H 4 ·H 2(O) was added to the mixture, and stirring was continued for 0.5 h. Then, the mixed solution was transferred to a polytetrafluoroethylene-lined autoclave and reacted at 220 °C for 16 h. After the reaction, it was naturally cooled to room temperature. The sample was filtered and washed several times with deionized water and absolute ethanol, and then transferred to an oven for vacuum drying for a certain period of time to obtain sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles.

[0048] (2) The sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticles obtained in step (1) were added to 2000 mL of deionized water, and ultrasonicated and stirred for 20 min. Then, 5.3125 g of surfactant CTAB was added and ultrasonicated for 20 min, and then 200 μL of pyrrole was added and stirred for 20 min until completely dissolved. Then, 2800 mL of 0.1 mol·L -1 ammonium persulfate (APS) solution was slowly added dropwise to the above solution under an ice-water bath, and a stirring polymerization reaction was carried out for 16 h. After the reaction, centrifugation was carried out, and the obtained product was alternately washed several times with deionized water and absolute ethanol by centrifugation, and then dried in an oven at 60 °C for 12 hours. The dark green powder obtained after thorough grinding was the sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticle composite, where the mass ratio of PPy in the composite catalyst was 18 ‰.

[0049] Figure 1 , according to the XRD pattern of the PPy thin-layer-coated sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticle composite prepared in Example 5, it can be seen that the XRD pattern of the sample in Example 5 was basically consistent with that of the sulfur-vacancy-containing Mn 0.2 Cd 0.8 S pattern, with matching characteristic peaks, while the peaks of PPy were basically absent, which was due to the low content of pyrrole. This indicated that the successful synthesis of the PPy thin-layer-coated sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticle composite did not change the crystal structure of the sulfur-vacancy-containing Mn 0.2 Cd 0.8 S monomer.

[0050] Figure 6 The SEM image of the PPy thin-layer-coated sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticle composite prepared in Example 5 is shown. It can be seen from the figure that the sulfur-vacancy-containing Mn 0.2 Cd 0.8S is a nanoparticle structure, and sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticle composite is also a nanoparticle structure, and the diameter of the composite is larger than that of sulfur-vacancy-containing Mn 0.2 Cd 0.8 S monomer, indicating that the two have been successfully compounded.

[0051] The sulfur-vacancy-containing Mn 0.2 Cd 0.8 S nanoparticle composite wrapped with PPy thin layer prepared according to Example 5 has a photocatalytic degradation efficiency of 91.7% for ciprofloxacin after visible light irradiation for 1 h. After visible light irradiation for 2 h, the yield of hydrogen peroxide is 1317.7 μM.

[0052] The above embodiments are only for illustrating the technical concept and characteristics of the present invention, and the purpose is to enable those who are familiar with this technology to understand the content of the present invention and implement it accordingly, and it cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit and essence of the present invention should be covered within the protection scope of the present invention.

Claims

1. A PPy thin layer wrapped with sulfur-containing vacancy Mn 0.2 Cd 0.8 The method for preparing S nanoparticle composite material is characterized in that: The following steps are involved: S1. Take Cd(NO3)2·4H2O, Mn(NO3)2·4H2O and thiourea, add them to a mixed solution of deionized water and ethylenediamine, and stir evenly; then add hydrazine monohydrate, stir evenly to obtain a mixed solution; after hydrothermal reaction, cool the mixed solution, wash, and dry it to obtain sulfur-containing vacancy Mn 0.2 Cd 0.8 S nanoparticles; S2. The sulfur-containing vacancy Mn 0.2 Cd 0.8 After S nanoparticles were mixed with deionized water, surfactant CTAB was added and ultrasonic treatment was performed. Pyrrole was then added and stirred until it was completely dissolved. Then, ammonium persulfate solution was slowly added dropwise to the above solution under an ice-water bath, stirred, and polymerized. Centrifugation, washing, and drying were performed to obtain sulfur-containing vacancy Mn coated with a thin layer of PPy. 0.2 Cd 0.8 S nanoparticle composites.

2. The sulfur-containing vacancy Mn wrapped by the PPy thin layer according to claim 1 0.2 Cd 0.8 The method for preparing S nanoparticle composite material is characterized by: In S1, the dosage ratio of Cd(CH3COO)2·2H2O, Mn(CH3COO)2·4H2O, thiourea, deionized water, ethylenediamine and hydrazine monohydrate is 0.0757-47.2801 g: 0.0201-12.5512 g: 0.0913-57.0923 g: 10-1000 mL: 10-1000 mL: 0.2-100 mL.

3. The sulfur-containing vacancy Mn wrapped by the PPy thin layer according to claim 1 0.2 Cd 0.8 The method for preparing S nanoparticle composite material is characterized by: In S1, the volume ratio of the deionized water to ethylenediamine is 1:

1.

4. The sulfur-containing vacancy Mn wrapped by the PPy thin layer according to claim 1 0.2 Cd 0.8 The method for preparing S nanoparticle composite material is characterized by: In S1, the specific conditions of the hydrothermal reaction are: reaction temperature is 160-220°C, and reaction time is 16-32 h.

5. The sulfur-containing vacancy Mn wrapped by the PPy thin layer according to claim 1 0.2 Cd 0.8 The method for preparing S nanoparticle composite material is characterized by: In S2, the sulfur-containing vacancy Mn 0.2 Cd 0.8 The dosage ratio of S nanoparticles, deionized water, CTAB, pyrrole, and ammonium persulfate is 0.0531 g-33.1500 g: 20-2000 mL: 0.0085 g-5.3125 g: 1-200 μL: 5-2800 mL.

6. The sulfur-containing vacancy Mn wrapped by the PPy thin layer according to claim 1 0.2 Cd 0.8 The method for preparing S nanoparticle composite material is characterized by: In S2, the concentration of the ammonium persulfate solution is 0.1 mol·L -1 .

7. The sulfur-containing vacancy Mn wrapped by the PPy thin layer according to claim 1 0.2 Cd 0.8 The method for preparing S nanoparticle composite material is characterized by: In S2, the specific conditions of the polymerization reaction are: reacting at room temperature for 8-16 hours.

8. A PPy thin layer wrapped with sulfur-containing vacancy Mn 0.2 Cd 0.8 S nanoparticle composite material, characterized by: The composite material is prepared by the method according to any one of claims 1 to 7, and the microstructure of the composite material is Mn containing sulfur vacancies. 0.2 Cd 0.8 The S nanoparticles are wrapped with a layer of PPy nanofilm; wherein the mass ratio of PPy in the composite material is 3‰-18‰.

9. Sulfur-containing vacancy Mn prepared by the method according to any one of claims 1 to 7 0.2 Cd 0.8 Application of S nanoparticle composites in degradation of ciprofloxacin in solution under visible light and production of H2O2 in pure water.